EFFECTS OF DIETARY CRUDE PROTEIN LEVELS ON INTAKE, DIGESTIBILITY, AND CRUDE PROTEIN BALANCE OF GROWING KOREAN NATIVE GOATS (CAPRA HIRCUS COREANAE) - J. H. Park; S. J. Kim; N. Y. Kim; S. Y. Jang; J. W. Lee; Y. S. Yun; S. H. Moon (Journal of Animal and Plant Sciences, 2018)
This study was conducted to determine the adequate dietary CP level for growing wethers by investigating the effect of dietary CP level on dry matter intake, apparent digestibility, and protein balance inKorean native goats. Each growing wether was fed three diets that were formulated to contain low (13%, T1), medium ( 15%, T2), and high (18%, T3) levels of CP based on dry matter. Dietary protein levels affected the apparent digestibility of CP, CP intake (CPI), urinary CP, digestible CP, and CP efficiency (p<0.05). The apparent CP digestibility increased linearly as dietary CP increased (T1=73.03%, T2=76.49%, T3=80.66%; p<0.05). The CPI and digestible CP for T3 ( 129.92g/d, 104.93g/d) were also higher ( p<0.05) than those for T1 (90.39g/d, 65.68g/d), in addition, urinary emission for T3 (55.23g/d) was higher (p<0.05) than that for T2 ( 27.11g/d). CP utilization efficiency for T2 ( 49.11%) and T3 (44.42%) were both higher (p<0.05) than that for T1 (2 6.14%). A strong linear relationship existed between CPI and digestible CP (p<0.001, 2 r =0.988). The results from this study suggest that an adequate CP level for achieving optimal growth performance of growing Korean native goats is 15% of dietary intake. The CP requirement for maintenance has been
Keywords: Crude protein level; Digestibility; Maintenance; Crude protein requirement; Korea native goat.